A guide to prenatal counseling regarding neurodevelopment in congenital heart disease - Lee, Fu‐Tsuen; Sun, Liqun; Freud, Lindsay; Seed, Mike (Prenatal diagnosis, 2023)
Advances in cardiac surgical techniques taking place over the past 50 years have resulted in the vast majority of children born with congenital cardiac malformations now surviving into adulthood. As the focus shifts from survival to the functional outcomes of our patients, it is increasingly being recognized that a significant proportion of patients undergoing infant cardiac repair experience adverse neurodevelopmental (ND) outcomes. The etiology of abnormal brain development in the setting of congenital heart disease is poorly understood, complex, and likely multifactorial. Furthermore, the efficacy of therapies available for the learning disabilities, attention deficit, and hyperactivity disorders and other ND deficits complicating congenital heart disease is currently uncertain. This situation presents a challenge for prenatal counseling as current antenatal testing does not usually provide prognostic information regarding the likely ND trajectories of individual patients. However, we believe it is important for parents to be informed about potential issues with child development when a new diagnosis of congenital heart disease is disclosed. Parents deserve a comprehensive and thoughtful approach to this subject, which conveys the uncertainties involved in predicting the severity of any developmental disorders encountered, while emphasizing the improvements in outcomes that have already been achieved in infants with congenital heart disease. A balanced approach to counseling should also discuss what local arrangements are in place for ND follow‐up. This review presents an up‐to‐date overview of ND outcomes in patients with congenital heart disease, providing possible approaches to communicating this information to parents during prenatal counseling in a sensitive and accurate manner. Key points What is already known about this topic? The heart is the organ most commonly affected by birth defects. Neurodevelopmental (ND) disorders frequently affect children with congenital heart disease, with those with genetic syndromes and single ventricle hearts most severely affected, although even mild forms of heart disease confer some risk. What does this review add? This review summarizes current knowledge regarding the prevalence, etiology, and risk factors for ND disorders in patients with congenital heart disease across the lifespan. Key information is presented as a reference for clinicians and parents following a prenatal diagnosis of congenital heart disease. We emphasize approaches to supporting families facing a new diagnosis of congenital heart disease.